Technology improvement on artificial Incubator system for tilapia (Oreochromis Niloticus) egg - Mohd Fareezman Zamzuri (2022)
Malaysia has gained demand in Nile Tilapia fish raw material. Incubation system is a established artificial incubation system for intensive fry production of Nile Tilapia (Oreochromis Niloticus). This study was carried out to create the new system by creating smart incubation system as an alternative incubation system for small-scale hatchery operators. Two incubation systems are used ie Smart Artificial system were compared with normal. Results showed that the amount of water used was significantly lower in Smart Artificial system with 70L of water compared to normal incubation system control with 15 000L of water at Aquaculture Extension Centre in Jitra, Kedah. The eggs hatching percentage was significantly higher in Smart Artificial system 89.17% compared to normal incubation system control 74.4%. Hatching tended to occur slightly earlier in the Smart Artificial system than normal incubation system control. After 10 days of rearing, the mean fry survival rate was highest in Smart Artificial 82.53% compared to the normal incubator system control 67.30%. The dissolved oxygen was significantly higher in Smart Artificial system 5.96 mg/l. The mean for the water temperature was lowest in Smart Artificial system 29.17ºC compared to normal incubation system control 30.02ºC recorded a high value. Further experiments indicated that 3000 eggs can be successfully hatched with a hatching rate of 89.17% and reared to swim-up fry in 70L size of Smart Artificial system with no water exchange. Smart Artificial system is best suited for incubation of late stage eggs and rearing of newly hatched larvae up to free swimming stage that called fry stage. The results indicate that the Smart Artificial system can be used as an alternative of artificial incubator system for Nile Tilapia eggs.